Approach to the knowledge, attitude and practice in reproductive health of male dogs with owner - Sánchez R., Alfonso (2021)
The animal health and welfare are tasks that should not be dissociated, and therefore they should be linked for a greater understanding and establishment of comprehensive health. Based on this, the importance of establishing reproductive health guidelines in intact adult dogs, through medical evidence, as well as investigating the parameters that value knowledge, attitude and practice in relation to responsible ownership. In the present study, surveys were conducted as a data collection technique to 50 dog keepers. In the reproductive health examination, higher frequencies of subclinical, prostate, and testicular abnormalities were identified in dogs older than 6 years of age as compared to younger animals (p<0.05). Prostate enlargement was observed in 75% of dogs. Regarding the knowledge and attitude in responsible pet ownership and reproductive health, the responses showed that they agreed with good practices, however, it was not fully reflected in daily activities.